Sculpture, Video, Performance. A Dialogue Between Harun Farocki and Bruce Nauman About the Image of the Artist as a Worker - Athanassopoulos, Vangelis (Ariadne, 2026)
This essay is a contribution to the debate about expanded cinema (Youngblood 1970, Bullot 2017). It attempts to test Giorgio Agamben’s concept of “pure mediality” (Agamben 1996) on the crossovers between contemporary art and the moving image (Dubois 2011, Bellour 2012) through a comparative analysis of the work by the German cinematographer Harun Farocki and the one by the American artist Bruce Nauman. The iconography of the artist at work introduces a questioning about the representation of human movement under the prism of the aesthetics of performance. These aesthetics combine methodological tools drawn from Agamben and from Farocki (Farocki 2007). The concept of “pure mediality” enables us to examine in a new way the articulation, in contemporary art, between performativity and reflexivity, and to elaborate a theoretical model of the relationship between image, gesture and discourse, which puts into question the traditional separation between the object of representation and the mediating process through which it is represented.